Design of robust controllers for plants with large dead time - Стопакевич, Андрей Алексеевич; Стопакевич, Алексей Аркадьевич (Eastern-European Journal of Enterprise Technologies, 2016)
The robust control system design problem for plants with large dead time is analyzed. Such plants are distributed in industry. The plants are hard controlled because controllers use past state of the plant output. The control quality analysis is provided with the help of direct, integral and frequency performance indexes. The analysis results show that the best design method is SIMC for PI-controller among classic controllers. Some better result gives PIDF design of the modified PID-controller with aperiodic filter, and frequency Matlab design of PI controller using the Smith predictor modified by Huang. The design of special model predictive controllers is not efficient for the plants with large dead time.